An Optimized Resonant-cap Ka-band IMPATT Oscillator for Broadband Communication - Laxmi Prasad Mishra; Mihir Narayan Mohanty; Sudarshan Chakraborty; Monojit Mitra (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Demand on capacity and band width increasing day-by-day in the area of wireless communication. One of the solutions is utilization of frequency bands for broadband communication that is related to satellite communication. Mostly Ka-band is used in satellite communication. In this paper, an attempt is taken to design an optimized resonant-cap Ka-band oscillator. To obtain oscillation from Ka-band IMPATT device. It has been embedded in a resonant cavity for which resonant cap structure is used. From this study, it is found that the supply D.C voltage from the top of the diode provides a matching network between the diode and the load to achieve maximum power. Keeping the breakdown voltage of the IMPATT diode fixed, the variation of bias current helps for detailed study and mechanically tuning has been done with variation of cap height, Cap diameter as well as by varying the position of the short using sliding short tuner and verified experimentally. Optimization result is made to get maximum output with maximum efficiency for an optimized cap height, diameter, and position of sliding short tuner. With these facts the work is presented difference tuning methods for resonant cap IMPATT oscillator.